Non-precision approach in manual mode - Коршунов, М. В. (Proceedings of National Aviation University (archive), 2013)
Considered is the method of non-precision approach of an aircraft in the manual mode with a constant angle of path. Advantage of this method consists in the fact that the construction of approach with a constant angle of path provides the stable path of flight. It is also considered a detailed analysis of the possibility of the approach by the above-mentioned method. Conclusions contain recommendations regarding the use of the described method of non-precision approach during training flights.